ASSRJ 2018
DOI: 10.14738/assrj.53.4262
|View full text |Cite
|
Sign up to set email alerts
|

Cashless Policy And Commercial Banks’ Profitabilty In Nigeria

Abstract: The study examines the effects of the adoption of cashless policy on the profitability performance of commercial banks in Nigeria. By using ATM and POS as proxy for the adoption of cashless policy and ROA and ROE as proxy for profitability and using the Ordinary least Square multiple regression analysis, the study reveals that there is a high positive correlation between the adoption of cashless policy and commercial bank profitability in Nigeria. The multiple regression analysis also revealed that the use of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 1 publication
1
13
0
Order By: Relevance
“…ATMs, internet banking, credit and debit cards, and other forms of digital banking reduce banks' expenses and increase their income, which has greatly increased their profitability (Akara, 2018;Gündoğdu & Taşkin, 2017).…”
Section: Literature Review and Theoretical Backgroundmentioning
confidence: 99%
“…ATMs, internet banking, credit and debit cards, and other forms of digital banking reduce banks' expenses and increase their income, which has greatly increased their profitability (Akara, 2018;Gündoğdu & Taşkin, 2017).…”
Section: Literature Review and Theoretical Backgroundmentioning
confidence: 99%
“…The return on asset (ROA) and return on equity (ROE) of banks would improve in the long run with the implementation of electronic banking (Yang et al, 2018). Electronic banking, such as ATMs, internet banking, credit and debit cards, lowers banks' expenditure and generates higher revenue, which has significantly improved banks' profitability (Aduda & Kingoo, 2012;Akara & Asekome, 2018;Gündoğdu & Taşkın, 2017;Itah & Emmanuel, 2014). However, Simpson (2002) demonstrates that electronic banking generated higher revenue for banks in the USA than in emerging markets, due to a strong information technology framework in the USA compared to developing countries.…”
Section: Empirical Reviewmentioning
confidence: 99%
“…On the other hand, the consistent results can be found in studies in some developing countries. Itah and Emmanuel (2014) and Akara and Asekome (2018) examined the impact of electronic banking in Nigeria. They found that electronic banking improved ROA and ROE of commercial bank in long run after the system of electronic banking is well-developed with the improvement of service delivery (Adewoye, 2013), cost effectiveness and wider coverage of electronic payment channels (Mustapha, 2018).…”
Section: Empirical Review On Electronic Payment and Bank Performancementioning
confidence: 99%
“…Although studies such as De Young et al ( 2007), Hernando and Nieto (2007), Onay and Ozsoz (2013) and Gündoğdu and Taşkın (2017) showed evidence that electronic banking services improved the performance of banks in developed countries, some studies (Khrawish & Al-Sa'di, 2011;Hosein, 2013;Gutu, 2014;Chen et al, 2019) showed contradictory findings in developing countries. But, Itah and Emmanuel (2014) and Akara and Asekome (2018) argue that the improvement of ROE can realised after the systems are well-developed in developing countries. Based on the research gap, we expect that electronic payments could enhance a bank's ROE.…”
Section: Hypotheses Developmentmentioning
confidence: 99%